As realizações de dativo no português falado em Teresina (PI): uma análise variacionista - Francisca da Cruz Rodrigues Pessoa (2017)
This Thesis aims at describing and analyzing, in Brazilian Portuguese spoken by Teresina (PI) inhabitants, the dative realizations in 1st, 2nd and 3rd persons, in order to evaluate whether the generalizations obtained based on the 3rd person datives are adequate to describe and explain the 1st and 2nd person datives in Brazilian Portuguese. The present study relies on the theoretical-methodological presuppositions of Variation Theory (LABOV [1972], 2008; 1994; 2001; 2010). The sample analyzed is comprised of 36 interviews, recorded from 2000 to 2003, which belong to the Database of Aspectos Gramaticais do Português Falado por teresinenses Project of the Federal University of Piauí (UFPI), organized by professors Maria Auxiliadora Ferreira Lima (UFPI) and Maria Anecy Calland Marques Serra (UFPI). Ten novel interviews recorded in 2015 were added to such set. The global corpus is stratified by social group, gender, level of education and age. We analyzed the occurrences of dative as asociolinguistic variable, considering as variants the clitic pronominal forms and the full pronominal forms, encompassing preposition+stressed pronoun. 307 occurrences were identified, 169 being of the cliticvariant and 138 being of prepositional variant. We noted significant difference between the three grammatical persons. The 1st person critical realization a percentage of 81% and relative weight (.84); the 2nd person one obtained 80% of occurrences and relative weight of (.88). The 3rd person one has the lowest occurrence percentage, 1%, and relative weight of (.02). The significant conditioning factors were verb person, verb type and social group. The non-significant ones were direct object realization, subject realization, direct object DP realization, preposition, gender, level of education and age. Our results show that the generalizations over the presence of dative clitics in Brazilian Portuguese, made based on the research on 3rd person clitics, do not extend to the 1st and 2nd person clitics, as the latter are more frequent and differ from the former with regard to their internal structure.